(untitled) (AYUSHDHARA, 2023)
An autoimmune multi-systemic condition called psoriasis has an effect on psychological and emotional health, including low self-esteem, stigma, and anxious mental states. The estimated global frequency is about 2%; however, it varies from nation to nation. A 32 years old female patient was diagnosed with psoriasis and she has suffering from voluptuous itching with a burning sensation mainly at night, brownish-red discoloration of skin and also scaly formation. After scratching sometimes oozing blood from the scalp, waist region and legs for the last 7 years. The patient was treated with different kind methods of treatment yet there was no agreeable outcome emerged. Therefore, the patient pursued homoeopathic treatment for a permanent recovery. A constitutional homoeopathic medicine Lycopodium clavatum 200CH was prescribed truly based on symptoms totality. The symptoms improved after the second prescription. According to homoeopathic principles, this led to an increasing the potency of Lycopodium clavatum 1M. After a few months of treatment, a noticeable outcome as well as a perceptible improvement in the PASI Index appeared. This instance demonstrates the beneficial benefits of homoeopathic constitutional treatment of psoriasis.